Examination of the Correlation Between Cyberbullying Behavior and the Feelings of Fanaticism of Local Football Fans - Özlem EKİZOĞLU; Cemal ÖZMAN; Osman GIDIK (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
The research aims to examine the relationship between local football team fans' feelings of fanaticism and cyber bullying behavior. 861 football spectators living in Bayburt province who support 5 local football clubs, namely Gürbüz Sports, Kurtuluş Sports, Konursu Sports, Çatıksu Gençlik Sports and Akşar Sports Club, participated in the research. As data collection tools; The "football fan fanaticism scale" developed by Taşktenpligil, Çankaya and Tunç (2014) and the "cyber bullying behavior scale of sports spectators" developed by Karaca (2019) were used. Data were collected via Google Form and analyzed in SPSS 21.0 program. Since the data did not show a normal distribution, the findings were obtained using the Kruskal-Wallis H test and Spearman's rho. As a result, the club with the highest audience tendency to think and act towards violence is Çayksu Gençlik Sports Club; the club with the highest audience score in corporate affiliation was Akşar Sports Club, and the club with the highest audience score in cyber bullying behavior was Kurtuluş Sports Club. It has been determined that there is a weak negative relationship between football fans' tendency to think and act towards violence, one of the sub-dimensions of fanaticism, and cyber bullying behavior, and in this case, as the tendency towards violence increases, cyber bullying decreases.